O04 Clinical and cost-effectiveness of ultrasound-guided intra-articular corticosteroid and local anaesthetic injection for hip OA: a randomised controlled trial (HIT). (20th April 2020) - Paskins, Zoe; Bromley, Kieran; Lewis, Martyn; Hughes, Gemma; Hughes, Emily; Cherrington, Andrea; Hall, Alison; Holden, Melanie; Oppong, Raymond; Kigozi, Jesse; Stevenson, Kay; Menon, Ajit; et al.
Abstract: Background: Evidence of the effectiveness of intra-articular corticosteroid injection for hip osteoarthritis (OA) is limited. The HIT trial compared the clinical and cost-effectiveness of an ultrasound-guided intra-articular hip injection (USGI) of 40mg triamcinolone acetonide and 4ml 1% lidocaine hydrochloride combined with best current treatment (BCT) with (i) BCT alone (primary objective) and (ii) an USGI of 5ml 1% lidocaine only combined with BCT (EudraCT:2014-003412-37). Methods: This was a pragmatic, three-parallel arm, single-blind, randomised controlled trial in adults with moderate-severe painful hip OA recruited from community musculoskeletal services and primary care. Participants were randomised equally to: (1) BCT alone, (2) BCT plus USGI triamcinolone/lidocaine, or (3) BCT plus USGI lidocaine only. Outcomes were collected postally at 2 weeks, 2, 4 and 6 months. The primary outcome was self-reported current hip pain intensity (0-10 numeric rating scale (NRS)) over 6 months (repeated measures analysis). Secondary outcomes included function (WOMAC), and, for cost-utility analysis, general health (EQ-5D-5L) and healthcare utilisation. 204 participants were required to detect a minimum difference of 1 point in mean pain NRS score between arms (1) and (2) with 80% power (5% two-tailed significance level, 15% loss to follow-up). Analysis was by intention-to-treat. Results: 199 participants were recruited (43% male, mean age 63 years), 67 to arm (1) and 66 each to arms (2) and (3). Primary outcome completion rates were 95% at 2 weeks, 94% at 2 months, 90% at 4 months, and 89% at 6 months. Greater mean improvement in hip pain intensity (0-10 NRS) over 6 months was seen with BCT plus USGI triamcinolone/lidocaine compared with BCT alone: -1.43 (95%CI -2.15, -0.72). Greater mean improvement in pain intensity was seen at 2 weeks (-3.17; -4.06, -2.28) and 2 months (-1.81;-2.71, -0.92), but not at 4 (-0.86;-1.78, 0.05) or 6 months (0.12; -0.80, 1.04). Participants treated with BCT plus USGI triamcinolone/lidocaine compared with BCT alone had greater mean improvement in function (WOMAC-F -5.47;(-9.41, -1.53)) over 6 months. There was no statistically significant difference in hip pain intensity over 6 months between BCT plus USGI triamcinolone/lidocaine compared with BCT plus USGI lidocaine (-0.52;-1.21, 0.18). There was one possible treatment-related serious adverse event: a participant with no signs of infection at randomisation died from endocarditis four months after USGI triamcinolone/lidocaine. BCT plus USGI triamcinolone/lidocaine was less costly (mean cost difference per participant £-161.59) and associated with significantly higher quality-adjusted life-years (QALYs) than BCT only over 6 months (mean difference 0.0477 (0.0257, 0.0699). Conclusion: USGI triamcinolone/lidocaine plus BCT leads to greater improvements in pain and function over 6 months in adults with hip OA than BCT alone, and was highly cost-effective. There was no significant difference in hip pain intensity between the groups receiving USGI triamcinolone/lidocaine and USGI lidocaine only, raising the possibility of a degree of placebo effect. Disclosures: Z. Paskins None. K. Bromley None. M. Lewis None. G. Hughes None. E. Hughes None. A. Cherrington None. A. Hall None. M. Holden None. R. Oppong None. J. Kigozi None. K. Stevenson None. A. Menon None. P. Roberts None. G. Peat None. C. Jinks None. N.E. Foster None. C.D. Mallen None. E. Roddy None.